The effects of free surfaces and molecular confinement on relaxation processes in thin polymer films - Yang, Haidong (2009)
Glass transition, physical aging and dielectric relaxation in ultra-thin polymer films (< 100 nm) were investigated using complementary techniques (ellipsometry and dielectric spectroscopy).